ORGANIZATIONAL REFORM OF REGENCY/CITY ELECTION COMMISSIONS IN WEST JAVA - Abdal (International Journal of Social Science, 2021)
This study aims to explore organizational reform at the Regency/City General Election Commission in West Java, both with regard to the existence of Regency/City KPU as the organizer of the General Election. as well as during the term of office of the commissioner. This study uses qualitative methods, descriptive analysis, case study strategies with steps for selecting topics and cases, reading literature, formulating research focuses and problems, data collection, data refinement, data processing, data analysis, data analysis process, theoretical dialogue, triangulation. findings, and conclusions of research results. data collection by observation, interviews, documentation and focus group discussion (FGD). Data analysis was carried out through data reduction procedures, data display and conclusion drawing/verification. Based on the results of the study, it can be concluded that the existence of the Regency/City General Election Commission is still needed as the organizer of the general election at the regional level; that there must be a change in the organization of the Regency/City General Election Commission in relation to the term of office of the commissioner from five years to 1.5 years for budget efficiency and performance effectiveness.